Causes and effects of poor communication in the construction industry in the MENA region - Suleiman, Akram (Journal of Civil Engineering and Management, 2022)
The construction industry in the Middle East and North Africa (MENA) faces many challenges throughout the project’s lifecycle; on top of these challenges is poor communication which occasionally results in project failure or at least time and cost overruns. A range of steps and methods must be taken to minimize the causes and effects of poor communication to enhance communication. The main aim of the study is to exploring poor communication in MENA construction industry and defining the causes and effects of poor communication from the perspective of consultants, clients, and contractors in small and medium enterprises in a developed region like MENA. Construction professionals from different project parties were asked to complete a questionnaire listing 32 causes and 21 effects of poor communication identified from the literature. The model was validated by Structural Equation Modelling SEM in terms of convergent and discriminant validities. The results revealed, that out of 54 cause and effect factors of poor communication, only 18 factors were retained. These causes and effects were ranked using the relative importance index RII. Results showed that all causes and effects are highly important, with RII above 0.6. The most important causes of poor communication are lack of communication procedure and training, followed by lack of adequate representation for project stakeholders. However, the least important cause of poor communication is a lack of understanding among the construction parties. Conversely, the most acute effects of poor communication are misinterpretation, followed by conflict among construction parties. However, the least important effect of poor communication is a late response to the disaster. Results and recommendations derived from this study represent the vital need of the MENA construction industry to focus on enhancing the current status of communication. The commitment of all project stakeholders to the drawn recommendations regarding the causes of poor communication will undoubtedly limit or reduce the effects of poor communication. Construction firms looking to improve their performance may benefit from the developed model.